Analisis Morfologi Eritrosit Packed Red Cell (PRC) Berdasarkan Waktu Penyimpanan Di UDD PMI Medan - Paska R Situmorang; Regina Tampubolon; Rica Vera Br.Tarigan (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2023)
Packed Red Cell (PRC) is made from whole blood by separating red blood cells from plasma using high speed centrifugation. Good PRC storage is at a shelf life of 35 days with a temperature of 2-6°C and must be maintained properly to ensure the morphological quality of erythrocytes. This study aims to determine the morphology of erythrocytes based on storage time with cross-sectional methods and descriptive analytical research design. The number of samples used was 45 PRC blood bags using the method of blood smear preparation with giemsa staining and observed under a 100x magnification microscope. Based on the results of day 0 research found most of the abnormal erythrocyte morphology, namely 40 blood bags (88.9%) and a small part had normal morphology as many as 5 blood bags (11.1%), the results of the study on days 10, 20 and 30 found abnormal morphology as many as 45 blood bags (100%). The occurrence of an increase in abnormal erythrocytes at 0 days is caused by the life span of erythrocytes that have reached the age of 120 days, the quality of staining, and environmental factors from donors, as well as previous studies. The presence of erythrocyte damage on days 10, 20 and 30 was caused by the quality of Giemsa staining, storage time and length of delay in making blood smears due to delays in sample delivery, and shipping temperature